1987
DOI: 10.1063/1.339460
|View full text |Cite
|
Sign up to set email alerts
|

Grain growth and grain size distributions in thin germanium films

Abstract: We have observed and characterized normal and secondary grain growth in thin films of germanium on silicon dioxide. Films were deposited on thermally oxidized silicon wafers, encapsulated with 1000-Å-thick sputtered SiO2 films and annealed in evacuated ampoules at 900 and 915 °C. After 5 min, the films had developed a columnar grain structure as a result of normal grain growth. The grain size distributions were lognormal with mean grain diameters of about 2.5 times the film thickness. The standard deviation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(81 citation statements)
references
References 22 publications
5
73
0
1
Order By: Relevance
“…Sometimes, this can even lead to a complete grain growth stagnation. Simulations have also shown that groove-induced stagnation leads to lognormal size distributions [9,[57][58]. Another possible reason for abnormal grain growth is that there are almost always grainorientation-specific driving forces for grain growth.…”
Section: Normal and Abnormal Grain Growth In Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, this can even lead to a complete grain growth stagnation. Simulations have also shown that groove-induced stagnation leads to lognormal size distributions [9,[57][58]. Another possible reason for abnormal grain growth is that there are almost always grainorientation-specific driving forces for grain growth.…”
Section: Normal and Abnormal Grain Growth In Thin Filmsmentioning
confidence: 99%
“…Despite the fact that two-dimensional normal grain growth can easily be modelled or simulated, and that in (2.4) practice thin films with structures as shown in figure 2.4a are very attractive candidates for testing those models, two-dimensional normal grain growth rarely occurs even in films with quasi-2D structures. In practice, grain structures of films that have undergone grain growth do not have grain size distributions that are well fit by Weibull distribution functions, but are instead well fit by lognormal grain size distributions [58][59][60]. Moreover, when grain growth leads to grain sizes significantly larger than the film thickness, it usually involves the favoured growth of a subpopulation of grains with specific crystallographic textures.…”
Section: Normal and Abnormal Grain Growth In Thin Filmsmentioning
confidence: 99%
“…Secondary grain growth has also been investigated in detail in a number of thin film systems [42][43][44][45][46][47]. For fcc metal films, the texture evolution during grain growth often favors (111)-textured driven grain growth has been studied extensively, both experimentally [42][43][44][45][46][47] and through computer simulations [48][49][50].…”
Section: -Abnormal and Secondary Grain Growthmentioning
confidence: 99%
“…It is to retnark here that the GSD of the film with n = 4 approaches a nearly perfect lognormal distribution on annealing for 240min, although the average grain size at this condition is only about the size of film thickness, 20nm. This is a premature stagnation of grain structure in view of the well established fact that the grain stagnation usually occurs at D -2.5 t [4].…”
Section: Resultsmentioning
confidence: 99%